2014
DOI: 10.1186/s12966-014-0123-y
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing weight loss treatment delivered in large versus small groups

Abstract: BackgroundBehavioral interventions for obesity are commonly delivered in groups, although the effect of group size on weight loss has not been empirically evaluated. This behavioral weight loss trial compared the 6- and 12-month weight changes associated with interventions delivered in a large group (LG) or small groups (SG).MethodsObese adults (N = 66; mean age = 50 years; mean BMI = 36.5 kg/m2; 47% African American; 86% women) recruited from a health maintenance organization were randomly assigned to: 1) LG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Questionnaires utilized in this study were previously validated within diverse samples and demonstrated good reliability within the present sample. To our knowledge, only one other study has reported on group dynamics within lifestyle interventions for obesity , and therefore this study adds useful information on the associations between group dynamics and weight loss, attendance, and adherence.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Questionnaires utilized in this study were previously validated within diverse samples and demonstrated good reliability within the present sample. To our knowledge, only one other study has reported on group dynamics within lifestyle interventions for obesity , and therefore this study adds useful information on the associations between group dynamics and weight loss, attendance, and adherence.…”
Section: Discussionmentioning
confidence: 94%
“…Although the association of group dynamics and treatment outcomes has been researched extensively within the psychotherapy literature, it remains a largely unstudied phenomenon within lifestyle interventions for obesity. In a year long obesity intervention using groups of approximately 10 and 30 participants, Dutton et al found that participants within smaller groups endorsed greater cohesion than those in larger groups. Group cohesion, however, did not impact weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive behavioral lifestyle interventions have been developed and are proven to reduce weight in clinical trials at levels that are beneficial for health [ 5 8 ]. The 2014 American Heart Association evidence-based guidelines on the treatment of obesity suggest that lifestyle interventions are most successful when they include face-to-face sessions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis controlling for site differences, group size was not found to be associated with mean weight loss [ 10 ]. In the single randomized trial conducted to date on this topic in obesity, Dutton and colleagues examined the effects of group size on engagement and weight loss [ 5 ]. Sixty-six participants were randomized to one group of 30 or to one of three smaller groups of 12 members.…”
Section: Introductionmentioning
confidence: 99%
“…Participants perceived the group component of the intervention as important to their weight loss success, because the group provided an environment for both social support (encouragement, advice for addressing challenges, shared weight loss goal) and accountability in meeting dietary and physical activity goals. The superior weight loss benefits of group versus individual therapy have been documented [27, 28] and previous studies have found that level of group engagement [35] and conflict [36] were associated with weight loss during interventions for obese adults from the general population. Our findings contribute to the existing literature in identifying multiple group process mechanisms that were important specifically to breast cancer survivors.…”
Section: Discussionmentioning
confidence: 99%